PENGARUH KOMUNIKASI INTERNAL, DUKUNGAN ORGANISASI, LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PERUSAHAAN XYZ - Djadi Nugroho, Wisnu; Ruswidiono, Wasisto (E-Jurnal Manajemen Trisakti School of Management (TSM), 2021)
XYZ Company is a company engaged in transportation and forwarder services. The purpose of this study was to examine the effect and nature of the relationship between employee performance and three influences, namely internal communication, organizational support, and work environment at XYZ Company . The population and sample in this study were 71 employees. This study uses a saturated sampling technique. Data was collected by distributing questionnaires to respondents. The data analysis method in this study is multyple linear regression processed. The results of this study are internal communication, organizational support and work environment affect employee performance.